Capturing the multiplicities of resilience through popular geopolitics: Aesthetics and homo resilio in Breaking Bad. (March 2017) - Grayson, Kyle
Abstract: In this article, Grove and Adey's (2015) call to capture the multiplicities of resilience through aesthetics is advanced by engaging with the first two seasons of the television series Breaking Bad . This engagement demonstrates that the relationality of geopolitics and mobility is important for resilience. To capture dynamics generated by the interplay of geopolitical contexts and resilient subjectivities through popular geopolitics, Jacques Rancière's aesthetics and the concept of the aesthetic subject are deployed. The emergence of homo resilio as a political subject within an imagined American heartland is presented to contextualise the aesthetic reading of Breaking Bad that follows. The character Walter White is presented as a paradigmatic example of homo resilio to map the geopolitics of this subject position. The paper concludes that race and gender feature at the intersections of homo resilio, geopolitics, and cultural criticism, reiterating the importance of popular geopolitics for capturing the multiplicities of resilience.